Holographic Writing of Forked Diffraction Gratings on the Surface of a Chalcogenide Glass Semiconductor - Nikolay A. Ivliev; Svetlana N. Khonina; Vladimir V. Podlipnov; Sergey V. Karpeev (Photonics, 2023)
We consider the formation of forked diffraction gratings on the surface of a multilayer structure based on chalcogenide glass semiconductors As2S3 and a-Se is. The distribution of electric field components upon interference of beams with different polarization states is analyzed theoretically. The possibility of direct holographic writing of diffraction gratings with a “forked” structure is demonstrated. The parameters of vortex laser beams generated by the microrelief formed are examined.